Inbreeding by Environmental Interactions Affect Gene Expression in Drosophila melanogaster - Kristensen, Torsten Nygaard (Copyright © 2006 by the Genetics Society of America, 2006)
Genomewide gene expression patterns were investigated in inbred and noninbred Drosophila melanogaster lines under benign and stressful (high temperature) environmental conditions in a highly replicated experiment using Affymetrix gene chips. We found that both heat-shock protein and metabolism genes are strongly affected by temperature stress and that genes involved in metabolism are differentially expressed in inbred compared with noninbred lines, and that this effect is accentuated after heat stress exposure. Furthermore we show that inbreeding and temperature stress cause increased between-line variance in gene expression patterns. We conclude that inbreeding and environmental stress both independently and synergistically affect gene expression patterns. Interactions between inbreeding and the environment are often observed at the phenotypic level and our results reveal some of the genes that are involved at the individual gene level. Our observation of several metabolism genes being differentially expressed in inbred lines and more so after exposure to temperature stress, together with lower fitness in the investigated inbred lines, supports the hypothesis that superiority of heterozygous individuals partly derives from increased metabolic efficiency.